The Role of Teachers in Realizing the Golden Generation Noble Character (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this study is to explain the role of the teacher in realizing a noble generation of gold. This research is a library research. The results in the study show that teachers have a strategic role in realizing a golden generation with noble character. Teachers can direct students to prepare the provisions needed in the era as the golden generation. The teacher provides direction and exemplifies attitudes, thoughts and behaviors that have a noble character and carry out daily activities.